How cryptomarket communities navigate marketplace structures, risk perceptions and ideologies amid evolving cryptocurrency practices - Childs, Andrew (Criminology & criminal justice, 2025)
Cryptomarkets are increasingly requiring users to purchase products with Monero (a ‘privacy coin’) to further obfuscate the digital trail of money compared to conventional cryptocurrencies (e.g. Bitcoin). This is the first study to explore how cryptomarket communities are used to facilitate norms and behaviours to expedite these emerging cryptocurrency practices. Through a qualitative analysis of Monero threads in a Reddit cryptomarket community (3451 total posts), this research illustrates how online communities often underpin the adoption of new technologies in cryptomarkets. The findings reveal: how the online community functions, adapts, and fails to support cryptocurrency transitions; the appraisal and contestation of cryptocurrency risks; and the ideological drivers and symbolic resources used to align community practices to adopt Monero. This research contributes to an understanding of the processes that underpin the constant evolution of online illicit markets as human and non-human elements are constantly re-assembled.